Supplementation with phytoestrogens and insoluble fibers reduces intestinal carcinogenesis and restores ER-β expression in Apc-driven colorectal carcinogenesis. Issue 1 (January 2020) - Luceri, Cristina; Femia, Angelo Pietro; Tortora, Katia; D'Ambrosio, Mario; Fabbri, Sergio; Fazi, Marilena; Caderni, Giovanna
Abstract : Supplementation with phytoestrogens and insoluble fibers has been reported to reduce duodenal polyps in colectomized familial adenomatous polyposis patients, with a mechanism involving, at least in part, upregulation of estrogen receptor-β subtype, whose expression is lowered during intestinal tumorigenesis. These data suggest a protective effect also in the colon, the main target organ for tumorigenesis in familial adenomatous polyposis and a major cancer type in non-familial (sporadic) cancers. Therefore, we tested whether a similar preparation might reduce tumorigenesis in the colon of Pirc rats (F344/NTac-Apc am1137 ) mutated in the Apc gene and thus, like familial adenomatous polyposis patients, spontaneously developing multiple tumors in the colon. We first demonstrate that estrogen receptor-β expression in Pirc rat colon is significantly down-regulated compared to age-matched wt rats. Then, Pirc rats aged 1 month were treated for 3 months with Adipol (Adi), a patented preparation containing phytoestrogens and insoluble fibers. Colon tumorigenesis was significantly reduced by Adi treatment (colon tumors/rat were 5.3 ± 0.8 and 2.9 ± 0.3, Mucin Depleted Foci/rat 127 ± 6.6 and 97.1 ± 8.6 in Controls and Adi-treated rats, respectively, means ± SE, P < 0.01). The treatment also normalized colon proliferation pattern along the crypt and significantly increased apoptosis in colon tumors. Estrogen receptor-β expression was increased by Adi treatment, especially in the tumors. These positive effects suggest that Adipol may be exploited as a chemopreventive agent to reduce cancer risk in familial adenomatous polyposis patients and to postpone prophylactic colectomy. Moreover, given the similarities between familial adenomatous polyposis and sporadic colorectal cancer, it might also be used as chemopreventive agent in colorectal cancer patients at risk. Abstract : Supplemental Digital Content is available in the text.